2021
DOI: 10.1002/emp2.12488
|View full text |Cite
|
Sign up to set email alerts
|

Electronic pulmonary embolism clinical decision support and effect on yield of computerized tomographic pulmonary angiography: ePE—A pragmatic prospective cohort study

Abstract: Objective Multiple professional societies recommend pre‐test probability (PTP) assessment prior to imaging in the evaluation of patients with suspected pulmonary embolism (PE), however, PTP testing remains uncommon, with imaging occurring frequently and rates of confirmed PE remaining low. The goal of this study was to assess the impact of a clinical decision support tool embedded into the electronic health record to improve the diagnostic yield of computerized tomography pulmonary angiography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In relation to PE, evidence-based clinical decision support systems (CDS) have been shown to improve diagnostic yield [19,20], and WA Health provides these in relation to CTPA [18] although they may not always be used. In patients suspected of PE, the obvious way forward is to embed a pre-test probability assessment in the ED workflow using electronic health records to present CDS related to PE diagnostic strategies to the ED physician [46]. Such systems have been shown to decrease advanced imaging use, improve the diagnostic yield of CTPA, and reduce non-adherence to pre-test probability assessment [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to PE, evidence-based clinical decision support systems (CDS) have been shown to improve diagnostic yield [19,20], and WA Health provides these in relation to CTPA [18] although they may not always be used. In patients suspected of PE, the obvious way forward is to embed a pre-test probability assessment in the ED workflow using electronic health records to present CDS related to PE diagnostic strategies to the ED physician [46]. Such systems have been shown to decrease advanced imaging use, improve the diagnostic yield of CTPA, and reduce non-adherence to pre-test probability assessment [46].…”
Section: Discussionmentioning
confidence: 99%
“…In patients suspected of PE, the obvious way forward is to embed a pre-test probability assessment in the ED workflow using electronic health records to present CDS related to PE diagnostic strategies to the ED physician [46]. Such systems have been shown to decrease advanced imaging use, improve the diagnostic yield of CTPA, and reduce non-adherence to pre-test probability assessment [46]. Similar international research has suggested that mandating the recording of Wells scores and Ddimer values on CTPA request forms increases diagnostic yield [47], although such policies may oversimplify the role of clinical judgement.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical Decision Support (CDS) systems have been well studied; however, results have varied substantially, with multiple noting nonsignificant changes to positivity rates 6-8 .…”
Section: Discussionmentioning
confidence: 99%
“…7 EHR-embedded decision support can improve physician decision-making, 17,18 even in busy EDs. 17,19 But effect durability has not been well studied. To be sustainable, practice innovations must continue their impact in the absence of their initial promotion and must adapt to changing conditions and evidence.…”
Section: Introductionmentioning
confidence: 99%
“…EHR-embedded decision support can improve physician decision-making, even in busy EDs . But effect durability has not been well studied.…”
Section: Introductionmentioning
confidence: 99%